Public journalism in the Philippines problems and prospects - Brion, Daniele Nicole D. (Quezon City College of Mass Communication, University of the Philippines Diliman, 2007)
"This thesis explores public journalism in the Philippines by looking at its practice, problems and prospects, as well as its practitioners. Public journalism aims to reengage the citizenry back into public debate and deliberation. By looking at this philosophy, the researchers were also able to looks at the current state of print and broadcast journalism. The thesis examines the efforts done by the Center for Community Journalism and Development, the Philippine Press Institute, the Kapisanan ng mga Brodkaster ng Pilipinas. Qualitative analysis and a case study on the Bandillo ng Palawan, a community paper, were used as research strategies. Data were collected from interviews, newspapers, public reports, and Internet documents. This thesis reinforces the view that public journalism is a means to improve the profession and not an end in itself. Rejuvenating the profession and restoring its respect from the public can be achieved by public journalism as it advocates a return to journalism's tenets of fairness, accuracy, justice and truth while employing creative means such as public fora, citizen polls, focused groups discussions, media alliances and partnerships with non-media organizations."
Vita.
Thesis (A.B. Journalism)--University of the Philippines Diliman